A STUDY ON DIFFERENT PELLET FORMATION TECHNIQUES AND ITS EVALUATION PARAMETERS-A REVIEW - A., REHANA BEGUM; S., GANESH N.; CHANDY, VINEETH (International Journal of Current Pharmaceutical Research, 2019)
This review article deals with the various pelletization techniques utilized in the pharmaceutical industry for spheroidal particle production i.e., pellet for mainly oral administration which can be further formulated into several other dosage forms such as tablets, capsules or can be administered as such. Now-a-days oral administration has become the most versatile, convenient and common route of drug administration which ultimately focuses on patient compliance. The technique which is setting horizon in pelletization is “Extrusion Spheronization” because of its simple and easy steps involved in pellet production in a faster way. This review also includes the characterization and evaluation of pellets to ensure its quality, safety and efficacy to give out the required therapeutic activity after administration.